2009
DOI: 10.5137/1019-5149.jtn.2705-09.1
|View full text |Cite
|
Sign up to set email alerts
|

A new entity: chiari zero malformation, and its surgical method

Abstract: Recently, Iskandar et al described "Chiari Zero malformation" to characterize some kind of syringomyelia that exhibits classic Chiari-type symptoms with little to no herniation, but there is some dilemma about whether it is actually present. We presented a 38-year-old-man with a diagnosis of cervical syringomyelia. In his neurological examination, there was monoparesia at the left leg together with hypoesthesia below thoracal 7. He had initially been treated with syringopleural shunting successfully. Nine mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…Successful surgical treatment requires appropriate patient selection and identification of the optimal procedure for the individual patient. PCF decompression with or without dura reconstruction is the most common procedure performed in these pa-tients, improving the clinical symptoms in most (around 80%-90%) CM-I, 11,49 CM-0, 21,22 and CM-1.5 cases, 48 but additional procedures are often needed, 16,56 and some complications can occur (9%-42% of cases). 11,49 Furthermore, some patients do not report any significant improvement.…”
Section: Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful surgical treatment requires appropriate patient selection and identification of the optimal procedure for the individual patient. PCF decompression with or without dura reconstruction is the most common procedure performed in these pa-tients, improving the clinical symptoms in most (around 80%-90%) CM-I, 11,49 CM-0, 21,22 and CM-1.5 cases, 48 but additional procedures are often needed, 16,56 and some complications can occur (9%-42% of cases). 11,49 Furthermore, some patients do not report any significant improvement.…”
Section: Impactmentioning
confidence: 99%
“…These studies have indicated that individuals with CM-0 or CM-1.5 display an overcrowded PCF and symptoms similar to CM-I patients. However, since TH is generally absent in CM-0 21,22,41,47 and the position of the brainstem in CM-1.5 is between that seen in CM-I and that seen in CM-II, 26,48 there is a debate over the relevance and even the existence of these newer categories. 35 The radiographic measurement of TH may not be the best anatomical feature to use for CM diagnosis.…”
mentioning
confidence: 99%
“…The definition of CM-I based on TP has come under scrutiny since several studies employing quantitative measurements have shown that TP does not correlate with the severity of symptoms and the degree of cerebellar TP below the foramen magnum is not heritable in multiplex families with CM-I patients [1417]. Patients with pronounced TP may present clinically asymptomatic, while patients with minimal or no TP may present with marked symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…in the recent years, several studies have showed that extracts of cigarette smoke inhibited the activity of Pon1 (2,9,21).…”
Section: Introductionmentioning
confidence: 99%